Hydrochemical dynamics on sub-Antarctic Marion Island - Stowe, Michael-James (Department of Environmental and Geographical Science, 2017)
Although sub-Antarctic maritime environments are some of the most sensitive regions to climate change, investigations into isotopic and hydrochemical dynamics on sub-Antarctic islands are limited. To address this, the Soft Plume River on sub-Antarctic Marion Island was sampled daily along an altitudinal gradient during an intense high-resolution 16-day field campaign in April/May 2015. Samples were analysed for stable isotopes (δ²H and δ¹⁸O) and major ions (Ca²⁺, Mg²⁺, K⁺, Na⁺, Cl⁻ , SO4²⁻, NO³⁻). In addition, stream water physicochemistry (pH, water temperature, dissolved oxygen and total dissolved solids) was monitored in situ at a single site in the stream at 5 minute resolution for the duration of the field campaign. Monthly precipitation δ²H and δ¹⁸O had mean values of -27.51‰ and -4.67‰ respectively. Stream water δ²H and δ¹⁸O values were significantly different to that of precipitation, with values ranging from -48.0‰ to -33.6‰ and from -7.6‰ to -5.6‰, respectively. Major ion concentrations were dominated by Na⁺ and Cl⁻, reflecting the overwhelming influence of the surrounding ocean on the island's stream water chemistry. This finding is consistent with previous studies on Marion Island and other maritime sub-Antarctic islands. Temporal variability in stream chemistry was assessed through daily sampling. Findings show that variation was predominantly controlled by precipitation. Following high precipitation amounts low stream water δ²H and δ¹⁸O values were recorded. This was likely the result of the "amount effect". Similarly, a decrease in ion concentrations was also observed following high rainfall amounts. This was because of stream dilution. Sampling along the stream revealed that variation in δ²H and δ¹⁸O and most major ions was largest at the highest site. This pattern is likely the result of an altitudinal precipitation gradient, with higher amounts of precipitation falling at the highest altitude site. High-frequency monitoring of stream water physicochemistry revealed the presence of diel oscillations. Stream pH, temperature and dissolved oxygen concentrations all exhibited diel cycles. Stream pH and temperature were characterised by afternoon maxima and night time minima, with dissolved oxygen following an inverse cycle. These results are the first time diel cycles have been observed for stream water on Marion Island. Taken together, results from this study revealed that the Soft Plume River exhibited a noticeable degree of variability and complexity, especially as results only represent stream water chemical dynamics over a limited range of annual hydroclimatic variation.